THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP , ORGANIZATIONAL SUPPORT, AND JOB SATISFACTION ON MOTIVATION AND EMPLOYEE PERFORMANCE - Achmat Maskurochman; Mulyanto Nugroho; Slamet Riyadi (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2020)
The purpose of this study was to analyze the effect of transformational leadership, organizational support, and job satisfaction on work motivation in improving employee performance. Descriptive research verification using the approach quantitative surveys and data collection by survey method with instrument of questionnaire with Likert scale of 1 to 5. The population of this research was the employees of in branch quarter of the Scout Movement in East Java obtained, while the sampling technique used is census method, so all population become a respondents in this study. Data analizing is performed using SEM AMOS 24 software. The results of this study where the transformational leadership, organizational support, and job satisfaction has a significant effect on work motivation, garthermoretransformational leadership, organizational support and job satisfaction has a significant effect on employee performance, lastly that work motivation has a significant effect on employee performance.